2011
DOI: 10.1111/j.1474-9726.2011.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of peripheral and systemic sex steroids on skeletal muscle quality in pre‐ and postmenopausal women

Abstract: SummaryAging is associated with gradual decline of skeletal muscle strength and mass often leading to diminished muscle quality. This phenomenon is known as sarcopenia and affects about 30% of the over 60-year-old population. Androgens act as anabolic agents regulating muscle mass and improving muscle performance. The role of female sex steroids as well as the ability of skeletal muscle tissue to locally produce sex steroids has been less extensively studied. We show that despite the extensive systemic deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 44 publications
(43 reference statements)
3
95
1
3
Order By: Relevance
“…Similarly, GH replacement therapy in older adults is associated with a high incidence of adverse effects, [189] and it does not appear to be any more beneficial to muscle strength than resistance training [189]. Finally, in one hormonal study that did measure muscle quality as both relative strength and CT attenuation, circulating concentrations of estrogen, DHEAS, and IGF-1 were correlated with muscle quality while testosterone and DHT (dihydrotestosterone) were not [190]. Regardless of the relationships, the efficacy of these hormones as exogenous treatment to improve muscle quality remains to be examined.…”
Section: Hormonal Interventionsmentioning
confidence: 91%
“…Similarly, GH replacement therapy in older adults is associated with a high incidence of adverse effects, [189] and it does not appear to be any more beneficial to muscle strength than resistance training [189]. Finally, in one hormonal study that did measure muscle quality as both relative strength and CT attenuation, circulating concentrations of estrogen, DHEAS, and IGF-1 were correlated with muscle quality while testosterone and DHT (dihydrotestosterone) were not [190]. Regardless of the relationships, the efficacy of these hormones as exogenous treatment to improve muscle quality remains to be examined.…”
Section: Hormonal Interventionsmentioning
confidence: 91%
“…In post-menopausal women, for instance, the force generating capacity of the muscle was less than that of pre-menopausal women with similar activity levels. This lower force generating capacity was not only due to muscle atrophy [24], but also a sudden decrease in specific tension (force per muscle cross-sectional area) during menopause [24,25]. The reduction in specific tension was at least to some extent attributable to an increased fat infiltration in the muscle of postmenopausal women [24] and a reduction in single fibre specific tension [26].…”
Section: Hormonesmentioning
confidence: 99%
“…Although the effects of androgens on muscle function have been evaluated extensively, the roles of estrogens in muscle have been largely unknown. Recent studies have revealed that the levels of estrogens are associated with muscle mass (McClung et al 2006, Sitnick et al 2006, Sugiura et al 2006, Pollanen et al 2011. Ovariectomized (OVX) mice fail to fully recover muscle mass after hindlimb suspension-induced muscle atrophy followed by reloading (McClung et al 2006).…”
Section: Introductionmentioning
confidence: 99%